If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -2y = 3 + -1y Solving 11 + -2y = 3 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 11 + -2y + y = 3 + -1y + y Combine like terms: -2y + y = -1y 11 + -1y = 3 + -1y + y Combine like terms: -1y + y = 0 11 + -1y = 3 + 0 11 + -1y = 3 Add '-11' to each side of the equation. 11 + -11 + -1y = 3 + -11 Combine like terms: 11 + -11 = 0 0 + -1y = 3 + -11 -1y = 3 + -11 Combine like terms: 3 + -11 = -8 -1y = -8 Divide each side by '-1'. y = 8 Simplifying y = 8
| g(-5)=(-56)-6 | | 40=x(14-x) | | 21x-30x-7=20 | | 53=10(u-93)+13 | | 3(2c+d)-4(c-d)+d^2= | | 3h^2-2=10 | | 13p+15p+15=43 | | y=8x-2/x^3 | | 16=8x-x^2 | | 3sinx=1-3cosx | | -20/t=-4 | | Y+8.71=3.8 | | 0.3x-0.5y=6.7 | | 2log^4=16 | | 87n+-11n+-85n=-27 | | 4/8=x/12 | | 0.25x+0.10(30-x)=5.58 | | Y-1/2=1/4 | | 11d+d-3d-4d=20 | | 3/8a=6 | | 11d+d+3d-4d=20 | | X-1/6=-1/2 | | -13y-19=20 | | 4x-5(0)=1 | | 3u+4u+2u+2=11 | | 6w+3(4w-2)=2(9w-3) | | 7X+2(x+2)=8-2(x-1) | | 2x^2+16x+59=0 | | 3(r+1)-7=2 | | 20-8/-3= | | 22=m/-2 | | m-8(1)=58 |